2002
DOI: 10.1002/ijc.10232
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus 16 load in normal and abnormal cervical scrapes: An indicator of CIN II/III and viral clearance

Abstract: The relation between human papillomavirus type 16 (HPV 16) viral load in cervical scrapes and development of highgrade cervical intraepithelial neoplasia (CIN II or III) was studied in a nested case-control study of women with normal cytology (group A) and in a cohort of women with abnormal cytology (group B). HPV 16 DNA load was determined using a quantitative real-time PCR assay. In group A, case women (women with CIN II/III, n ‫؍‬ 12) had a significantly higher viral load than control women (women with CIN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
189
1
10

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(221 citation statements)
references
References 22 publications
20
189
1
10
Order By: Relevance
“…Large studies on cervical smears suggested that persistent HPV infection, 21 cytological progression, [21][22][23][24] and the risk of a highgrade cervical lesion [21][22][23][24][25] are each associated with high HPV viral load in the cervix. As a consequence, viral load assessment was proposed to distinguish clinically relevant HPV infections in the cervix, 26 yet has only been assessed in a few studies of sites beyond the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Large studies on cervical smears suggested that persistent HPV infection, 21 cytological progression, [21][22][23][24] and the risk of a highgrade cervical lesion [21][22][23][24][25] are each associated with high HPV viral load in the cervix. As a consequence, viral load assessment was proposed to distinguish clinically relevant HPV infections in the cervix, 26 yet has only been assessed in a few studies of sites beyond the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…To test the quantity and quality of the extracted DNA and to demonstrate that the samples were free of inhibitory substances, real-time beta-globin gene PCR was performed on all samples as previously described. 25 HPV16 DNA load (VL) was determined in HPV16-positive samples and was defined as HPV16 copies per beta-globin gene copy. HPV16 copy numbers were determined by HPV16-specific quantitative real-time PCR (amplimer length 88 bp) using a LightCycler 480 (Roche, Mannheim, Germany), basically described before.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…Viral load has been suggested as a marker of nontransient infection, and high HPV load in smears with normal cytology has been associated with the risk of developing dysplasia and carcinoma in situ (CIS) van Duin et al, 2002;Dalstein et al, 2003;Moberg et al, 2004). However, it is not known whether high viral load is also predictive of invasive cervical cancer, as past studies have pooled the outcomes of invasive cancers together with earlier stages of the disease (Lorincz et al, 2002;Sherman et al, 2002Sherman et al, , 2003Sun et al, 2002;Dalstein et al, 2003;Gravitt et al, 2003).…”
mentioning
confidence: 99%